2014
DOI: 10.3389/fphys.2014.00234
|View full text |Cite
|
Sign up to set email alerts
|

Altered oscillatory cerebral blood flow velocity and autoregulation in postural tachycardia syndrome

Abstract: Decreased upright cerebral blood flow (CBF) with hyperpnea and hypocapnia is seen in a minority of patients with postural tachycardia syndrome (POTS). More often, CBF is not decreased despite upright neurocognitive dysfunction. This may result from time-dependent changes in CBF. We hypothesized that increased oscillations in CBF occurs in POTS (N = 12) compared to healthy controls (N = 9), and tested by measuring CBF velocity (CBFv) by transcranial Doppler ultrasound of the middle cerebral artery, mean arteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 52 publications
5
29
0
Order By: Relevance
“…This results from the combined effects of increased OAP in the LF band and increased LF transfer gain from OAP to OCBF in POTS. We have shown greatly increased CBF v in POTS when upright which is protected by an autoregulatory mechanism 18 which comprises properties of the vasculature that, in the absence of large environmental or metabolic changes, maintain CBF relatively unchanged despite changes in BP 25 . While the utility of these oscillations is poorly understood, our data suggest that OCBF interferes with NVC and that altered OCBF might serve as a marker for Brain Fog 8 in POTS.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…This results from the combined effects of increased OAP in the LF band and increased LF transfer gain from OAP to OCBF in POTS. We have shown greatly increased CBF v in POTS when upright which is protected by an autoregulatory mechanism 18 which comprises properties of the vasculature that, in the absence of large environmental or metabolic changes, maintain CBF relatively unchanged despite changes in BP 25 . While the utility of these oscillations is poorly understood, our data suggest that OCBF interferes with NVC and that altered OCBF might serve as a marker for Brain Fog 8 in POTS.…”
Section: Discussionmentioning
confidence: 82%
“…We recently observed greatly increased slow CBFv oscillations (<0.40 Hz) in POTS compared to controls during 70° upright tilt 18 suggesting that oscillatory CBF power interferes with cognition and neurovascular coupling. Therefore, we used incremental upright tilt and related increases in OCBF to decreases of functional hyperemia and cognitive performance in POTS, but not in healthy volunteers.…”
Section: Introductionmentioning
confidence: 93%
“…While other studies matched the groups by age (14,22), other studies did not (24). Furthermore, the majority of studies reported participants' ages central tendencies by mean, two studies utilized median instead (25,26). While other studies used a larger sample size (27), other used smaller sample sizes (28).…”
Section: Study Selectionmentioning
confidence: 99%
“…This led to conducting sensitivity analysis excluding this study. Furthermore, the overall mean ages of POTS and/or healthy group could not be calculated because data could not be accessed in other studies (28,32), because the median was utilized than the mean (25,26). Figure 2 illustrates eighteen of twenty eligible studies that compared HR outcomes between POTS versus Healthy participants.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Patients with POTS have acute changes in cognitive performance in response to orthostatic challenges, and these patients also have an increased prevalence of depression and higher levels of anxiety (Anderson et al, 2014 ). Impaired cerebral autoregulation may underlie upright cognitive dysfunction in POTS (Medow et al, 2014 ).…”
mentioning
confidence: 99%